Performance of sustainable concrete containing different types of recycled plastic. (15th December 2021) - Tayeh, Bassam A.; Almeshal, Ibrahim; Magbool, Hassan M.; Alabduljabbar, Hisham; Alyousef, Rayed
Abstract: The valorisation of plastic wastes has become a major environmental challenge. Problems stem from factors such as the limited reuse and difficulty of waste recycling. Plastic is an important type of solid waste with a strong environmental impact. This study aims to investigate and compare the impact of replacing fine aggregate by polyethylene (PE) and poly-ethylene terephthalate (PET) in concrete. The influence of those substances on the physical and mechanical properties of concrete was examined. Five concrete mixtures containing PET and PE was prepared as a partial replacement for fine aggregate with substitution levels 0%, 10%, 20%, 30% and 40%. Concrete was cast to investigate the fresh and hardened behaviour of concrete containing plastic in terms of workability, dry and fresh unit weight, compressive strength at different ages, flexural strength, tensile strength, ultrasonic pulse velocity, impact resistance and energy absorption. The experimental results showed a reduction in both wet and dry unit weight, whereas replacing the sand by plastic harmed the concrete strengths at varying rates. However, the addition of plastic improved the energy capacity and enhanced the impact resistance of concrete which proved that recycled plastic can be disposed of by limited ratios and therefore, can be effectively applied in industrial usage.